Sytuacja prawna muzułmanów w XIX-wiecznym Imperium Rosyjskim - Ludwiczak, Paweł (Studia Azjatystyczne, 2017)
The article discusses legal situation of the Muslim community under the legislation of the Russian Empire’s central governorates in the 19 th century. Regulations in force within that territory were similar to those applied in other governorates of the Imperial Russia. This research is of a general nature due to the fact that detailed elaboration on Muslims’ situation which would include their legal, civil and political limitations could become an extensive monograph, especially if one would take into consideration that different parts of the Russian territory implemented its own legal solutions enforced by the contemporary social and political situation.